Fodder Balance Study in Karnataka - Keshavaiah, K. V.; Kareemulla, K.; Girijesh, G. K.; Sainath Kumar, D. K.; , Rannorey; Koppalkar, B. G. (Indian Forester, 1995)
Fodder supply both in terms of quantity and quality will have bearing on the livestock performance. An exploratory study was conducted in Karnataka using three stage random sampling. In all eight social forestry ranges, 24 villages and 120 farmers were selected for this study. Almost half of the total fodder available in the sample villages is constituted by grass, while the other half is contributed by crop bye products. The requirement estimates suggest that, of the total requirement, 49 per cent is required in the form of grass, 44 per cent in the form of crop by-products and 7 per cent in the form of fodder. The over all fodder scarcity is 55 per cent in the study villages. The scarcity is higher in the study villages of Hassan, Gudibanda and Hospet Social Forestry Ranges. Greater efforts for raising fodder species in these Ranges may be initiated for improving the situation.